Log in to add a comment

## Answers

The Brainliest Answer!

As you can observe that

and

If we can make the terms equal, it will be perfect square.

(1) Subtract

(2) Add

**(x+a)(x+7a) =**and

**(x+3a)(x+5a) =**If we can make the terms equal, it will be perfect square.

**(1) subtract****(2) add**(1) Subtract

**-****->****->**(2) Add

**+****->****->**(x²+8ax+7a²)(x²+8ax+15a²)

now if they are to be perfect square then we must make each expression a sqaure by themselves so we add and subtract by the opposite

(x²+8ax+7a²)(x²+8ax+15a²)-(x²+8ax+7a²)

**8a²**

taking common we have

(x²+8ax+7a²)(x²+8ax+15a²-8a²)

(x²+8ax+7a²)(x²+8ax+7a²)= (x²+8ax+7a²)²

similarly we have

(x²+8ax+7a²)(x²_8ax+15a²)+(x²+8ax+15a²)

**8a²**

(x²+8ax+15a²)(x²+8ax+7a²+8a²)= (x²+8ax+15a²)²